2021
DOI: 10.1038/s41598-021-96597-w
|View full text |Cite
|
Sign up to set email alerts
|

Loss of the ciliary protein Chibby1 in mice leads to exocrine pancreatic degeneration and pancreatitis

Abstract: Primary cilia protrude from the apical surface of many cell types and act as a sensory organelle that regulates diverse biological processes ranging from chemo- and mechanosensation to signaling. Ciliary dysfunction is associated with a wide array of genetic disorders, known as ciliopathies. Polycystic lesions are commonly found in the kidney, liver, and pancreas of ciliopathy patients and mouse models. However, the pathogenesis of the pancreatic phenotype remains poorly understood. Chibby1 (Cby1), a small con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…The global Ift88 homozygous mutant mice present with absent or shortened pancreatic cilia, which in the pancreas exhibits as reduced pancreas mass with collagen deposition, progressive acinar cell loss, and ductal hyperplasia with pancreatic cyst formation [ 16 ]. These exocrine defects are consistent with phenotypes seen in knockout mouse models of ciliary protein Chibby1 or pancreas-specific kinesin family member 3A ( Kif3a ), an essential gene for cilia formation [ 43 , 72 ]. Proposed mechanisms for these pancreatic morphological changes include defective exocytosis of zymogen granules, intrapancreatic activation of digestive enzymes such as carboxypeptidase, and activation of transforming growth factor β and mitogen-activated protein kinase kinase/extracellular signal-regulating kinase pathways [ 41 , 43 , 72 ].…”
Section: Primary Cilia In Pancreas and Isletssupporting
confidence: 67%
See 2 more Smart Citations
“…The global Ift88 homozygous mutant mice present with absent or shortened pancreatic cilia, which in the pancreas exhibits as reduced pancreas mass with collagen deposition, progressive acinar cell loss, and ductal hyperplasia with pancreatic cyst formation [ 16 ]. These exocrine defects are consistent with phenotypes seen in knockout mouse models of ciliary protein Chibby1 or pancreas-specific kinesin family member 3A ( Kif3a ), an essential gene for cilia formation [ 43 , 72 ]. Proposed mechanisms for these pancreatic morphological changes include defective exocytosis of zymogen granules, intrapancreatic activation of digestive enzymes such as carboxypeptidase, and activation of transforming growth factor β and mitogen-activated protein kinase kinase/extracellular signal-regulating kinase pathways [ 41 , 43 , 72 ].…”
Section: Primary Cilia In Pancreas and Isletssupporting
confidence: 67%
“…In humans, primary cilia in the pancreas were first reported in β-cell tumor cells in 1964 [ 45 ]. So far, in human islets, only β- and α-cells have been documented to have primary cilia [ 42 , 45 ], whereas in the exocrine pancreas, primary cilia have been identified on ductal and centroacinar cells in both human and mouse [ 16 , 27 , 29 , 43 ]. RNA sequencing studies have demonstrated robust expression of cilia-related genes across cell types in mouse and human pancreas and islets, whose expressions are dynamically modulated by metabolic conditions such as hyperglycemia and diabetes mellitus [ 46 - 49 ].…”
Section: Primary Cilia In Pancreas and Isletsmentioning
confidence: 99%
See 1 more Smart Citation
“…We considered that 21d was the time point when CP injury was the severest in our study based on Demols criteria. Interestingly, the pancreatic parenchyma was replaced by a large amount of adipose tissue at 28d after surgery, namely lipomatosis (26). In order to verify the correlation between the mouse CP model constructed by pancreatic duct ligation and human CP, we collected three clinical samples of patients with CP caused by obstructive etiologies and three normal pancreatic samples for research.…”
Section: Discussionmentioning
confidence: 99%
“…Masson and Sirius red staining showed that fibrosis appeared from 7d, peaked on 21d, and still existed at 28d. However, due to lipomatosis (26), the fibrotic area decreased compared with that at 21d (Figures 3A, H). We collected some pancreatic tissues from clinical CP patients with a background of obstructive etiologies and human nonmalignant pancreatic patients for the HE, Masson and Sirius red staining, which exhibited obvious fibrosis and parenchymal loss (Figure 3B), and the percentage of fibrosis area in human CP specimen was closer to that at 21d in mice (Figures 3H, I).…”
Section: Cp Induced By Partial Ligation Of Pancreatic Duct Can Simula...mentioning
confidence: 91%